PROFIL PENGGUNAAN OBAT PADA PASIEN STROKE ISKEMIK PADA PASIEN DI POLI NEUROLOGI - Dedi Dedi; Darwin Syamsul; Resya Tiranda Siregar (Akademi Keperawatan Yarsi Samarinda, 2023)
Background:Stroke is one of the main causes of mortality. WHO defines stroke as a spatial neurological disorder with sudden onset, lasting more than 24 hours without any cause and causing serious long-term disability in Indonesia and the United States. Objectives; This study aimed to determine the profile of ischemic stroke drugs usage in patients of Aceh Tamiang Hospital and the use of types of drugs given to ischemic stroke patients.Method; This study was non-experimental prospectively by using a questionnaire on ischemic stroke patients in October 2020. The data was processed using Microsoft Excel.Results; The results of 26 respondents and the drugs issued in October for the neurology clinic at Aceh Tamiang Hospital obtained antiplatelet drugs, namely aspirin 80mg/tab with a total of 238 drugs (38.3%) and pletaal 50mg/caplet with a total of 42 drugs (6.7%). The neuroprotectant group was pirassetam 80mg/tab with 140 drugs (22.5%). The antihyperlipidemic group of the drug simvastatin 5 mg/tab totaled 21 drugs (3.4%). The antihypertensive drug class was amlodipine 10mg/tab total 28 drugs (4.5%), amlodipine 5mg/tab total 56 drugs (8.9%), captopril drug type 25 mg/tab total 63 drugs (10.2%), the type of drug furosemide dose 40mg/tab the amount of 35 drugs (5.6%).Conclusion; Drugs that were widely used in patients with ischemic stroke are the antiplatelet group, namely aspirin 80mg/tab obtained 238 tablets (38.3%), the neuroprotectant class of the drug piracetam 800mg/cap were 140 caplets (22.5%), the antihypertensive group amlodipine 5mg/tab were 56 tablets (8.9%), the antihyperlipidemic group of the simvastatin 5mg/tab were 21 tablets (3.4%).